A Review on Glassy and Rubbery Polymeric Membranes for Natural Gas Purification. Issue 2 (4th February 2021) - Farnam, Marjan; bin Mukhtar, Hilmi; bin Mohd Shariff, Azmi
Abstract: A comprehensive overview of membrane technology used for natural gas purification and other gas separation applications including methods, materials, and results described in previous studies is presented. Different membrane categories are elaborated thoroughly followed by comparisons made between glassy and rubbery polymeric membranes. Various approaches to improve membrane separation performance, such as incorporation of inorganic fillers and blending technique, are discussed. Gas separation in different membranes, e.g., glassy/rubbery polymer blend membranes, mixed matrix membranes, and polymeric blend mixed matrix membranes, are considered. Adopted techniques by researchers to solve existing issues in membrane fabrication and performance are explained in detail. Abstract : The application of membranes is an effective method for natural gas purification since acid gases like CO2 and H2 S need to be separated from natural gas in order to increase its heating value and reduce pipeline corrosion. A complete overview of a variety of gas separation membranes is given, discussing different glassy and rubbery polymeric membranes along with other membrane types for gas separation purposes.